Report on 41st International Conference on Sino-Tibetan Languages and Linguistics - Bradley, David (2024)
On 17 September there was an all-day symposium on Mediaeval Tibeto-Burman languages, organised by Nathan Hill of Harvard University. This comprised twelve presentations on a variety of languages including Tibetan, Tangut, Naxi, Lepcha and Muya, mostly based on text materials and discussing a variety of orthographic, phonological, syntactic, lexical, discourse and cultural issues.